Accelerated C# 2008 - Nash, Trey (Apress : Imprint: Apress, 2007)
Many books introduce C#, but if you don't have the time to read 1,200 pages, Accelerated C# 2008 gives you everything you need to know about C# 2008 in a concentrated 500 pages of must-know information and best practices. C# 2008 offers powerful new features, and Accelerated C# 2008 is the fastest path to mastery, for both experienced C# programmers moving to C# 2008 and programmers moving to C# from another object-oriented language. You'll quickly master C# syntax while learning how the CLR simplifies many programming tasks. You'll also learn best practices that ensure your code will be efficient, reusable, and robust. Why spend months or years discovering the best ways to design and code C# when this book will show you how to do things the right way, right from the start? Comprehensively and concisely explains both C# 2005 and C# 2008 features Focuses on the language itself and on how to use C# 2008 proficiently for all .NET application development Concentrates on how C# features work and how to best use them for robust, high-performance code.